2017
DOI: 10.1097/md.0000000000008367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast-conserving surgery with mastectomy in locally advanced breast cancer after good response to neoadjuvant chemotherapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 45 publications
5
44
0
13
Order By: Relevance
“…Asian women have relatively smaller breasts compared with women in Western countries [ 7 ]. Thus, TM rates among women receiving NACT in Asia have been high [ 8 ]. Therefore, the number of Taiwanese patients with breast cancer receiving NACT followed by TM is high [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian women have relatively smaller breasts compared with women in Western countries [ 7 ]. Thus, TM rates among women receiving NACT in Asia have been high [ 8 ]. Therefore, the number of Taiwanese patients with breast cancer receiving NACT followed by TM is high [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of Taiwanese patients with breast cancer receiving NACT followed by TM is high [ 9 ]. The effect of postchemotherapy pathologic tumor stages (ypT), postchemotherapy pathologic nodal stages (ypN), or overall pathologic American Joint Committee on Cancer (AJCC) stages would be valuable for further adjuvant treatment in Taiwan or Asia because most patients in Taiwan still receive TM after NACT [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term survival rate among early breast cancer women without NAC who undergo BCS was the same as that among women who undergo radical mastectomy [6][7]. However, several studies have demonstrated no signi cant difference in long-term survival or local recurrence rates between women who underwent BCS and those who underwent radical mastectomy after NAC [8][9]. Although predictive factors for local recurrence in these NAC-treated patient groups have not yet been clari ed yet, the higher local recurrence risk of NAC than of adjuvant chemotherapy is controversial.…”
Section: Introductionmentioning
confidence: 88%
“…In all of these trials, not only was there no inferiority for BCS versus mastectomy regarding local recurrences, distant metastases, and overall survival but also many studies showed benefits for breast conservation therapy (BCT) over mastectomy. Besides, some trials demonstrated a slightly more favorable outcome in patients with positive nodes treated with BCS; however, the differences were not statistically significant [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%